Glosa do wyroku Sądu Najwyższego PK II 290/11 z dnia 28 czerwca 2012 r. - Jankowski, Krzysztof J. (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Ruling of the Supreme Court from 28 June 2012 case PK II 290/11 could be perceived as stating a primacy of the principle of protection of employees over the rules of representation of legal entity which are ius cogens of commercial law. It was ruled that an employment relationship of an employee who was the Management Board member was changed by the mere behavior of the bodies of company. On a basis of Art. 210 of Commercial Companies Code a Management Board or its member cannot represent the company in relations with members of the Board. This paper presents a critical view on the indicated ruling, which appears to be based on values protection of employee rather than on the valid provisions of law, what is hardly acceptable from the legal system’s perspective.
Keywords: prawo pracy; aksjologia; ochrona pracowników; Sąd Najwyższy; wykładnia funkcjonalna